Riddah Sebagai Sebab Putusnya Perkawinan Serta Implikasinya Terhadap Nafkah Anak - Muhammad Al Faruq (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
Muslim does not become an infidel as long as he maintains his faith and Islam by not falling on any of the kinds of riddah or infidelity. Riddah is to do things that break Islam either by converting or something else, while the Perpetrator is called an apostate infidel. Riddah is divided into three kinds: Riddah words such as berating Allah, opposing or protesting to Allah, and putting Rasulullah to rest. Riddah deeds such as worshipping idols, the sun, and animals. It's like believing that a God is an object, a spirit, or a light. The marriage contract can be damaged if it occurs from both husbands or wives doing Riddah either by word, deed or belief. Providing for children for parents is mandatory for both boys and girls, who are young or ignorant children who cannot distinguish things and have not been able to stand alone. if one of the husbands and wives falls into a riddah either because of words, deeds or impossibility then the marriage is void. May refer back as long as the wife's iddah period is still there. By returning to Islam again. If a wife has been finished three times and the husband wishes to refer back then it must be by marriage contract. Then if one of the husbands and wives of his marriage is damaged by apostasy due to the impact on the livelihood of the child according to the thought of Sheikh Abdullah Al-Harary in the book of Bughyatut Tholib, the book of Shari'ul Bayan is obligatory for one of the husbands and wives to provide for him both sons and daughters, the ignorant and the disabled, the sick and the healthy.